Numerical Assessment of Pipe Pile Response under Seismic Excitation - Al-Jeznawi, Duaa; Jais, ISMACAHYADI Mohamed; Albusoda, Bushra S.; Khalid, Norazlan (Al-Nahrain Journal for Engineering Sciences, 2023)
The axial capacity and pile transference of loads under static loading have both been well reported, but further research is needed to understand the dynamic lateral responses. The pile load imposed during an earthquake may increase, but the soil’s ability to support it may fall as a side effect of the vibration leading to more settlement. The key objective of this work is to identify what led to the substantial lateral destruction of the piles during the seismic event due to the kinematic effects. These failures were related to discontinuities in the subsoil as a result of sudden changes in soil strength due to shaking. The kinematic stresses exerted in a single pipe pile constructed in two sand layers under two different situations (dry and saturated states) are investigated in this study using numerical modeling. The bending moments were higher in the saturated sand soil than in the dry one which may be attributed to liquefaction. Generally, the acceleration increased through the loose layer (from bottom to top), and then significantly settled within the dense layer. It could be shown that using this modeling, one can estimate how a pile foundation will behave under "kinematic" loading driven by earthquakes. Therefore, the design and installation of drilled aluminum or steel piles in sand soil could make use of these present observations.